2017
DOI: 10.1007/s00181-017-1277-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dark side of tax policy: an analysis of the interactions between fiscal illusion and the shadow economy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
1
9
0
2
Order By: Relevance
“…Aside from these effects of transparency on trust, some authors, such as Buehn, Dell’Anno, and Schneider (2017), consider that the lack of transparency impacts on the loss of confidence, which in turn triggers fiscal illusion. Furthermore, agency theory shows that higher levels of information reduce information asymmetries, which limits potential conflicts of interest between principals and agents, and increases confidence in politicians (Araujo & Tejedo-Romero, 2016).…”
Section: Literature Review On Trust In Governmentmentioning
confidence: 99%
“…Aside from these effects of transparency on trust, some authors, such as Buehn, Dell’Anno, and Schneider (2017), consider that the lack of transparency impacts on the loss of confidence, which in turn triggers fiscal illusion. Furthermore, agency theory shows that higher levels of information reduce information asymmetries, which limits potential conflicts of interest between principals and agents, and increases confidence in politicians (Araujo & Tejedo-Romero, 2016).…”
Section: Literature Review On Trust In Governmentmentioning
confidence: 99%
“…Following Buehn et al (2017), we specify extended versions of MIMIC models that include, among the determinants of the indicators ( Y ), and observed exogenous causes ( X ). Accordingly, we have solved a relevant issue in the use of MIMIC specification to economics application, that is, the omission of some direct effects of causes on indicators.…”
Section: Mimic Approach and Datamentioning
confidence: 99%
“…Full details on our model extension are available from authors upon request. See Buehn et al (2017) for the formal derivation of the extended version of the MIMIC model.…”
Section: Notesmentioning
confidence: 99%
“…Their study showed that the tax system is more (less) progressive when taxes and public expenditures are perceived less (more) and that an increase in the median voter's income may positively or negatively affect tax progressivity, depending on whether fiscal illusion is pessimistic or optimistic. Some new and very interesting aspects of fiscal illusion have recently been brought to attention in the Buehn, Dell'Anno, and Schneider (2018, pp. 1609-1630 analysis of interactions between fiscal illusion and the shadow economy.…”
Section: Current Lines Of Research On Fiscal Illusion and Its New Aspectsmentioning
confidence: 99%